2005
DOI: 10.1517/14712598.6.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet transplantation for treating diabetes

Abstract: Pancreatic islet transplantation is one of the options for treating diabetes and has been shown to improve the quality of life of severe diabetic patients. Since the Edmonton protocol was announced, islet transplantation have advanced considerably, including islet after kidney transplantation, utilisation of non-heart-beating donors, single-donor islet transplantation and living-donor islet transplantation. These advances were based on revised immunosuppression protocols, improved pancreas procurement and isle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 182 publications
1
30
0
Order By: Relevance
“…Recently We introduced a large amount of DI for maintaining patency of pancreatic duct for the collagenase delivery as Sutherland et al demonstrated that islet autotransplantation is much more effective than allotransplantation (22) well as protecting islets and exocrine tissue from cold ischemic injury (12). Actually, DI could significantly and our results with islet autotransplantation support their observation.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Recently We introduced a large amount of DI for maintaining patency of pancreatic duct for the collagenase delivery as Sutherland et al demonstrated that islet autotransplantation is much more effective than allotransplantation (22) well as protecting islets and exocrine tissue from cold ischemic injury (12). Actually, DI could significantly and our results with islet autotransplantation support their observation.…”
Section: Discussionsupporting
confidence: 67%
“…Approximately 1 ml/g pancreas of ET-Kyoto soluThe quality of pancreatic tissue retrieved from CP tion (Otsuka Pharm Factory Inc., Naruto, Japan) was patients undergoing total or partial pancreatectomy is administered intraductally before preservation in oxyinferior from the pancreas retrieved from deceased genated perfluorodecalin (11,12). For the UW group, the donors.…”
Section: The First Demonstration That Islets Isolated Frommentioning
confidence: 99%
See 1 more Smart Citation
“…32 Liberase HI (Roche, Indianapolis, Ind) or collagenase NB with neutral proteases (Serva Electrophoresis GMbH, Heidelberg, Germany) was continuously infused into the pancreas graft. 33 For pancreas digestion, we used the Ricordi method. 34 If pellet volume was larger than 15 mL, islet purification was performed using the COBE 2991 cell processor (CaridianBCT, Inc, Lakewood, Colo) with continuous density gradient.…”
Section: Islet Preparation and Evaluationmentioning
confidence: 99%
“…However, because we have very limited number of such donors in Japan, it is not possible to perform islet transplantation with brain-dead heartbeating donors. In order to initiate an islet transplantation program in Japan, we need to seek new donor resources (7).…”
mentioning
confidence: 99%